Pulmonary alveolar proteinosis: Case report of rare diffuse lung disorder in pediatric age group - Vipulkumar Gandhi; Shashank Kadam (Indian Journal of Respiratory Care, 2022)
Nonspecific symptoms and variable clinical course are a few of the hurdles in diagnosing pulmonary alveolar proteinosis (PAP). Lack of accessible health care and efficient health infrastructure, including diagnostic and treatment facilities, are the major challenges for early detection and prompt management of PAP in developing countries such as India. A 6-month-old child was brought to the tertiary health care center for cough, dyspnea, and intermittent fever. The history of third-degree consanguineous parents was evident. The patient had a history of evolving respiratory complaints at the age of 4 months, for which she was hospitalized for 12 days. There was a relapse of similar symptoms within 2 weeks of discharge and required readmission. The patient was cyanosed with signs of severe respiratory distress. Chest X-ray revealed bilateral diffuse alveolar infiltration. High-resolution computed tomography imaging showed diffuse interstitial thickening with adjacent ground-glass opacities along with crazy-pavement appearance involving both lungs. With flexible bronchoscopy, bronchoalveolar lavage (BAL) was performed. Congenital PAP was confirmed with periodic acid–Schiff -positive proteinaceous extracellular globules on smear. The child was intubated and mechanically ventilated during a hospital stay to treat uncontrollable respiratory failure. The child succumbed on the 28th day of admission despite repeated therapeutic BAL procedures and systemic corticosteroids. The possibility of missed/delayed diagnosis of PAP is widespread in resource-limited health-care settings. Postnatal onset of PAP should be suspected in every child with chronic respiratory distress and failure to thrive with diffuse alveolar infiltrates.